Residensi Analisis Masalah Kesehatan pada Program Gizi Keluarga di Dinas Kesehatan Kabupaten Jayapura - Rut R. Wanimbo; M Atollah Isfamdiari (Malahayati Nursing Journal, 2023)
ABSTRACT Increasing the MCH Degree is still the main goal in the Ministry of Health's strategic plan to be achieved in 2019 because of the low MCH degree in Indonesia, including the Jayapura District Health Office, even more specifically in the Community Nutrition Program. This residency is to gain work experience and nutrition improvement activities through institutions in the form of sustainable nutrition programs and new programs. The research used is the Urgency, Seriousness and Growth Method. Research Results: Based on the results of ultrasound that has been carried out, it can be seen that the priority problems in the Community Nutrition Program at the Jayapura District Health Office are problems related to the administration of Fe3 tablets to pregnant women with a score of 125, Vitamin A coverage with a score of 60 and the provision of PMT DPT to pregnant women with a score of 48. Based on the results of ultrasound that has been carried out, it can be seen that the priority problems in the Community Nutrition Program at the Jayapura District Health Office are problems related to the administration of Fe3 tablets to pregnant women with a score of 125, Vitamin A coverage with a score of 60 and the provision of PMT DPT to pregnant women with a score of 48. it was found that in the field of public health programs, the priority problem obtained by the USG method and the search for the root cause of the problem using the fishbone method was found to be the provision of Fe3 to pregnant women which is still not evenly distributed by all pregnant women so that it can have an impact on the health of children under five. Keywords: Residency, Public Health Nutrition Program  ABSTRAK Peningkatan Derajat KIA masih menjadi tujuan utama dalam renstra Kementerian Kesehatan yang ingin dicapai pada tahun 2019 karena masih rendahnya derajat KIA di Indonesia, termasuk Dinas Kesehatan Kabupaten Jayapura, bahkan lebih khusus lagi pada Program Gizi Masyarakat. Tujuan: Residensi ini untuk mendapatkan pengalaman kerja dan kegiatan peningkatan gizi melalui kelembagaan berupa program gizi berkelanjutan dan program baru. Residensi ini untuk mendapatkan pengalaman kerja dan kegiatan peningkatan gizi melalui kelembagaan berupa program gizi berkelanjutan dan program baru. Penelitian yang digunakan adalah Metode Urgensi, Keseriusan dan Pertumbuhan. Berdasarkan hasil USG yang telah dilakukan dapat diketahui bahwa masalah yang menjadi prioritas Program Gizi Masyarakat di Dinas Kesehatan Kabupaten Jayapura adalah masalah yang berkaitan dengan pemberian tablet Fe3 pada ibu hamil dengan skor 125, Cakupan Vitamin A dengan skor 60 dan pemberian DPT PMT pada ibu hamil dengan skor 48. Ditemukan bahwa di bidang program kesehatan masyarakat, masalah prioritas diperoleh dengan metode USG dan pencarian untuk akar permasalahan dengan menggunakan metode tulang ikan ditemukan pemberian Fe3 pada ibu hamil yang masih belum merata oleh semua ibu hamil sehingga dapat berdampak pada kesehatan anak balita. Kata kunci:  Residensi, Program Gizi Kesehatan Masyarakat